The Peculiarities of Institutionalization of Public Relations in RA - Melkonyan, Nvard (Journal of Sociology: Bulletin of Yerevan University, 2012)
The article is devoted to the problems of public relations technologies in the context of the democratic transformations in Armenia. The author analyzes the existing approaches to the relationship of PR and democracy. According to the first: PR is not only an applied science and practice of reputation management, but also a unique tool for democracy, which increases the transparency of public-political and economic life, is an important tool for achieving consensus in society. The second approach draws attention to the trend of increasing the use of manipulative technologies in the meantime increasing of democratization level of society. The author brings the main problems that are preventing or retarding the development of PR-technologies in Armenian society.